Peningkatan Kadar Trigliserida pada Serum Lipemik terhadap Asam Urat Metode Uricase - ridwansyah, fatthiyyahkaamilaridwansyah (Jurnal Kesehatan Siliwangi, 2024)
The quality of the serum can be affected by several factors such as hemolyzed, icteric, and lipemic serum. These factors might cause inaccurate test results, for example that lipemic serum can increase uric acid level. This study aims to determine whether or not there is an effect of triglyceride level in lipemic serum and to determine how much triglyceride level can affect uric acid level using the uricase method. This study was conducted in May 2024 at the Clinical Chemistry Laboratory of Medical Laboratory Technology, Poltekkes Bandung. The research method is a laboratory experiment with a statistical group comparison research design. The sample in this study was serum from 6 students of Medical Laboratory Technology, Poltekkes Kemenkes Bandung with the criteria of not hemolyzed, not icteric, and not lipemic. The serum was made lipemic by adding egg yolk so that the triglyceride level varied between 461 to 2492 mg/dL. In the lipemic serum, blood uric acid level were examined using the uricase method. The results showed that uric acid level in lipemic serum increased along with increasing triglyceride level. The results of the General Linear Model (GLM) Statistical Test showed that lipemic serum with triglyceride level of 1028 mg/dL had an effect, while lipemic serum with triglyceride level of 461 to 546 mg/dL did not affect uric acid level using the uricase method. The conclusion of this study is that triglyceride levels starting from 1028 mg/dL have an influence on increasing uric acid levels using the uricase method by 97,08%.